Berberine Reshapes the Balance of the Local Renin-Angiotensin System by Modulating Autophagy under Metabolic Stress in Pancreatic Islets - Huang, Chenghu; Lei, Pan; Peng, Caibi; Li, Min; Guo, Yifei; Li, Xuefeng (Journal of the Renin-Angiotensin-Aldosterone System, 2021)
Hypothesis/Introduction. Berberine, a natural compound, has multiple pharmacological activities to promote islet function. We hypothesized that berberine could reshape the local renin-angiotensin system (RAS) balance to ameliorate the development of obesity via the modulation of autophagy. Materials and methods. After 8 weeks of administration of intragastric berberine to ob/ob mice, metabolic parameters, islet structure, and the angiotensin-converting enzyme 2 (ACE2) expression were detected. Additionally, ACE2 knockout (ACE2KO) mice were fed a low-fat diet for 16 weeks. Furthermore, we measured changes in the islet ultrastructure by transmission electron microscope (TEM) and protein expression of LC3 and SQSTM1/p62 by immunohistochemistry in ob/ob and ACE2KO mice. Results. Prolonged exposure to palmitate increased the expression of ACE and AngII type 1 receptor (ATR1) and decreased the ACE2 expression, which was partly offset by berberine. In ob/ob mice, berberine increased in tolerance to glucose, improved abnormal β-cell and α-cell distributions, upregulated ACE2 expression, and decreased autophagosomes and the expression of LC3 and SQSTM1/p62. Autophagosomes and expression of LC3 and SQSTM1/p62 were increased in ACE2KO mice. Conclusions. We demonstrated that berberine may improve the pancreatic islet function by regulating local RAS-mediated autophagy under metabolic stress.